Who runs the AEA? - Kevin D. Hoover; Andrej Svorenécík (Duke University, Center for the History of Political Economy (CHOPE), 2020)
The leadership structure of the American Economics Association is documented using a biographical database covering every officer and losing candidate for AEA offices from 1950 to 2019. The analysis focuses on institutional affiliations by education and employment. The structure is strongly hierarchical. A few institutions dominate the leadership, and their dominance has become markedly stronger over time. Broadly two types of explanations are explored: that institutional dominance is based on academic merit or that it based on self-perpetuating privilege. Network effects that might explain the dynamic of increasing concentration are also investigated.
Keywords: A11; B29; D72; 330; American Economic Association; prosopography; academic networks